2007
DOI: 10.1083/jcb.200709111
|View full text |Cite
|
Sign up to set email alerts
|

Par3 functions in the biogenesis of the primary cilium in polarized epithelial cells

Abstract: Par3 is a PDZ protein important for the formation of junctional complexes in epithelial cells. We have identified an additional role for Par3 in membrane biogenesis. Although Par3 was not required for maintaining polarized apical or basolateral membrane domains, at the apical surface, Par3 was absolutely essential for the growth and elongation of the primary cilium. The activity reflected its ability to interact with kinesin-2, the microtubule motor responsible for anterograde transport of intraflagellar trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
88
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(102 citation statements)
references
References 30 publications
10
88
1
3
Order By: Relevance
“…Recent findings have also localized Par3, Par6, and atypical protein kinase C to primary cilia. These proteins seem to be important in ciliogenesis, perhaps through their interactions with critical ciliary proteins such as KIF3A and Crumbs3a (13,14). This is the first report to show that Cdc42 and Tuba, a Cdc42 GEF, also contribute to ciliogenesis in epithelial cells.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Recent findings have also localized Par3, Par6, and atypical protein kinase C to primary cilia. These proteins seem to be important in ciliogenesis, perhaps through their interactions with critical ciliary proteins such as KIF3A and Crumbs3a (13,14). This is the first report to show that Cdc42 and Tuba, a Cdc42 GEF, also contribute to ciliogenesis in epithelial cells.…”
Section: Discussionmentioning
confidence: 75%
“…We previously found that the exocyst coimmunoprecipitated and colocalized with Par3 (5), a main component of the Par complex that consists of Par3, Par6, atypical protein kinase C, and Cdc42 (11,12). In addition to their studied function at cell-cell contacts, the Par complex has been immunolocalized to primary cilia and has been shown to be necessary for ciliogenesis (13,14). It is known that the exocyst is regulated by multiple Rho and Rab family GTPases (reviewed in 15), which, like the exocyst, play central roles in cell polarization, morphogenesis, membrane trafficking, cell growth, and development (16,17).…”
mentioning
confidence: 99%
“…Par3, as discussed, was (Sfakianos et al, 2007). To test for a possible exocyst-Par3 interaction, we performed double labeling immunofluorescence microscopy by using antibodies against Par3 and the exocyst component Sec8.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that the PDZ protein Par3 localizes to the tight junction and primary cilium and knockdown of Par3 inhibits primary ciliogenesis (Sfakianos et al, 2007). Given a similar defect in ciliogenesis in the Sec10 knock- Figure 5.…”
Section: The Exocyst and Par3 Colocalize And Coimmunoprecipitatementioning
confidence: 99%
See 1 more Smart Citation